Non-representational theory in the South African Geography FET CAPS - Shaylen Naidoo (African Journal of Teacher Education and Development, 2025)
Background: The South African Geography Further Education and Training Phase (FET) Curriculum and Assessment Policy Statement (CAPS), despite its progressive aims, often implicitly reinforces a representational view of geographical knowledge, creating tension with non-representational theory’s (NRT) emphasis on process, affect and embodied experience. This presents how a curriculum focused on prescribed content and measurable outcomes can genuinely foster a deeper, more lived engagement with geographical phenomena.